2017
DOI: 10.1038/ncomms14055
|View full text |Cite
|
Sign up to set email alerts
|

Submesoscale transition from geostrophic flows to internal waves in the northwestern Pacific upper ocean

Abstract: With radar interferometry, the next-generation Surface Water and Ocean Topography satellite mission will improve the measured sea surface height resolution down to 15 km, allowing us to investigate for the first time the global upper ocean variability at the submesoscale range. Here, by analysing shipboard Acoustic Doppler Current Profiler measurements along 137°E in the northwest Pacific of 2004–2016, we show that the observed upper ocean velocities are comprised of balanced geostrophic flows and unbalanced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
134
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(154 citation statements)
references
References 49 publications
18
134
2
Order By: Relevance
“…We do not observe a distinct seasonal cycle in EKE wavenumber spectra, in contrast to recent studies that show higher energy within the submesoscale range during winter (Callies et al, 2015;Qiu et al, 2017). Submesoscale motions have a variety of generation mechanisms including mixed layer instability, direct wind forcing, or Charney instability, all of which are sensitive to surface mixing and hence show a seasonal dependence (McWilliams, 2016).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…We do not observe a distinct seasonal cycle in EKE wavenumber spectra, in contrast to recent studies that show higher energy within the submesoscale range during winter (Callies et al, 2015;Qiu et al, 2017). Submesoscale motions have a variety of generation mechanisms including mixed layer instability, direct wind forcing, or Charney instability, all of which are sensitive to surface mixing and hence show a seasonal dependence (McWilliams, 2016).…”
Section: Discussioncontrasting
confidence: 92%
“…This is at least partly due to contrasting coastlines: at 25°N, the FC is constrained within a channel and unable to sustain large meanders, and mesoscale eddies that form upstream are sheared apart as they are advected through the narrowing and shoaling channel (Fratantoni et al, 1998). The observed slopes are similar to those reported by Callies and Ferrari (2013) in the Gulf Stream extension but steeper than in the Kuroshio (k À2.3 ; Qiu et al, 2017) and in the subtropical North Pacific (k À2 ; Callies & Ferrari, 2013). Indeed, the EAC system is unique among WBCs for its large EKE-to-KE ratio (Boland & Hamon, 1970;Godfrey et al, 1980).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Indeed, a flattening of the KE spectrum at scales smaller than 20 km due to an increased contribution of ageostrophic internal waves in the Gulf Stream region has been reported by Callies and Ferrari (). Further, recent decompositions of regional high‐resolution models (Capet et al, ), and one‐dimensional ship‐track data have confirmed steep (shallow) scaling of rotational (divergent) modes (Bühler et al, ; Qiu et al, ; Rocha et al, ), with hints at the aforementioned transition in the slope of the KE spectrum (Bühler et al, ).…”
Section: Interpretation and Conclusionmentioning
confidence: 93%
“…This emphasizes the different impacts of SBMs and IGWs in terms of KE budget. Further results from Callies et al (), Rocha, Chereskin, et al (), Rocha, Gille, et al (), and Qiu et al () indicate IGWs and SBMs are both characterized by a strong seasonality. On one hand, SBMs are much more energetic than IGWs in winter, when surface frontal instabilities at small‐scale (such as mixed‐layer instabilities) are more efficient because of the large mixed‐layer depths (Callies et al, ; Mensa et al, ; Qiu et al, ; Rocha, Gille, et al, ; Sasaki et al, ; Su et al, ).…”
Section: Introductionmentioning
confidence: 89%